PENERAPAN MODEL PEMBELAJARAN EXPERIENTIAL LEARNING TERHADAP AKTIVITAS BELAJAR SISWA PADA PELAJARAN PENATAAN BARANG DAGANG - Hendra, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe research problem of research is the low of stuents’ learning activity on the eleventh grae of students marketing class in SMK Negeri 3 Pontianak. The purpose of this research is to find out the effect of experiental learning model to students’ learning activity on goods commerce arragement subject the method usedd un thid research is experiment method on pre-experiment design from, and research planning used in this research is one group pretest- post test design. The subject of this research is theeleveth grade students of pm2 in SMK Negeri 3 Pontianak. The process of deciding the class was while the researcher did teaching practice in SMK Negeri 3 Pontianak.the tools of ddata collecting are dirrect observation and doamentation study. Based on the result of data analysis, the students learning activity mean before has been given thetreatment was 68,15, categorized as good enough. Where as the students’ learning activity mean score after has been given the treatment was 78,72 categorize as good, and it is higher than mean score before has been given the treatment. This showed that was offect of experiental learning model to students learning activity.Keywords : Learning Activity, Experiental Learning.